Attitudes, Beliefs, and Perceptions on Cannabis Among Older Adults Aged 65 and Older: A cross-sectional Survey - Alex M. Kleidon; Andrew M. Peterson; Ilene Warner-Maron; Allen Glicksman (SAGE Publishing, 2023)
Objective: With the rise of medical and recreational cannabis use among older adults, concerns about the potential risks and benefits of cannabis use are increasing. This pilot study aimed to determine the attitudes, beliefs, and perceptions of older adults toward cannabis as a medicinal product, to establish a foundation for future research on how healthcare providers communicate with this population regarding cannabis. Methods: A cross-sectional survey was conducted on adults aged 65 and older living in Philadelphia. The survey included questions related to participants' demographics, knowledge, attitudes, beliefs, and perceptions of cannabis. Participants were recruited via flyer distributions, publications in newsletters, and a local newspaper. Surveys were conducted from December 2019 through May 2020. Quantitative data were presented using counts, mean, median, and percentages, and qualitative data were analyzed by categorizing common responses. Results: The study aimed to recruit 50 participants, of whom 47 met the requirements, and had their data analyzed, resulting in an average age of 71 years. The majority of participants were male (53%) and Black (64%). Seventy-six percent of participants considered cannabis a highly important treatment for older adults, and 42% considered themselves highly knowledgeable about cannabis. Over half of the participants reported being asked about tobacco (55%) or alcohol (57%) use by their PCP compared to 23% being asked about cannabis. Participants indicated that they most commonly turned to the internet and social media for information about cannabis, while only a small number mentioned relying on their primary care physician (PCP) for such information. Discussion: The results of this pilot study highlight the need for accurate and reliable information about cannabis for older adults and their healthcare providers. As the use of cannabis as a therapy continues to rise, it is crucial for healthcare providers to address misconceptions and encourage older adults to seek out evidence-based research. Further research is needed to explore healthcare providers' perceptions of cannabis therapy and how they can better educate older adults.